(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The article deals with the issue of English for Specific Purposes (ESP) revealing its different features described by a number of scholars. It expresses various reliable judgments on how to differentiate ESP courses from other similar ones, what constitutes absolute and variable characteristics of the term, what aspects to be considered while organizing these lessons, as well as specifications of its sub-divisions.